Organização das práticas de cuidados paliativos à pessoa idosa em comunidades vulneradas - Matheus Rodrigues Martins (2023)
The aging process does not occur homogeneously in society, but is influenced by historical, cultural, and socioeconomic aspects. Additionally, it is necessary to deal with the subjectivation of the elderly amidst the discourse of "active and healthy aging" proclaimed by the State and health organizations, articulated within the neoliberal political-economic context. Thus, there is a need to consider forms of care that ensure the quality of life of the elderly who face life-threatening conditions and do not place them within the realm of productivity as perceived by this policy. Therefore, Palliative Care (PC) emerges as a care modality aimed at improving the quality of life of individuals facing life-threatening diseases and their families/caregivers. In the Brazilian context, although the National Palliative Care Policy was approved in 2023, it has not yet been enacted. Consequently, there is still a need to expand basic discussions on PC, such as guidelines for financing, integrating the topic into professional education/training, and providing necessary support for its applicability. Thus, issues surrounding PC gain greater significance when considering communities in conditions of vulnerability, where the characteristics of the social and environmental context to which the population is exposed are considered determinants and conditions for the emergence and perpetuation of health inequities. The objective of this study is to understand the configuration of PC practices offered to the elderly within the household context, in the scope of vulnerable communities. This is a descriptive, exploratory research with a qualitative approach, conducted in the homes of patients under PC care provided by the university extension project "Comunidade Compassiva" (Compassionate Community) in the Rocinha and Vidigal favelas, in the municipality of Rio de Janeiro/RJ, Brazil. The participants of this research were individuals involved in PC for the elderly within the project, including volunteer healthcare professionals and local volunteers. Data collection utilized observation and semi-structured interviews. Discourse Analysis, inspired by Foucault, was used for evaluation. The results of this study indicate that PC practices for the elderly within vulnerable favela communities are shaped by the incipient production of public policies specifically aimed at relieving human suffering among individuals facing life-threatening conditions in Brazilian territory, combined with the historical, social, and cultural context of favela territories. Therefore, the delivery of PC to this population emerges through the micropolitics of resistance born from the knowledge and powers circulating in this context, permeating the individuals involved in these cares, constituting their discourses and social practices. These findings suggest that beyond fostering non-governmental health assistance initiatives, there is a need for advancements in the development of public PC policies grounded in the principles of universality, comprehensiveness, and equity, to integrate this care approach across all points of the Health Care Network (RAS) and also encompass favela territories. Additionally, it becomes imperative to understand the concept of health as expanded, considering the territorial dynamics and their social determinants and conditions of health.